The Company's Financial Performance Pre and Post IPO on The Indonesia Stock Exchange - Firman Siregar; Noer Azam Achsani; Bayu Bandono (School of Business, IPB University (SB-IPB), 2024)
An initial public offering (IPO) decision always had financial, accounting, and operational ramifications for the company. After an IPO, however, a company's performance typically declined, whereas there should have been an improvement in the company's performance when it went public. Good corporate performance could also be reflected in the company's financial performance. The purpose of this study was to compare the financial performance of companies before and after their initial public offerings (IPO). The research sample consisted of 31 companies that had an initial public offering in 2019, with financial reporting data from three years prior to the IPO and three years after the IPO. The methods of analysis employed were descriptive analysis and the Wilcoxon Signed Rank Test. After an initial public offering, the overall financial ratios examined in the study varied significantly. After their IPOs, the companies' performance declined (Return On Asset (ROA), Return on Equity (ROE), Debt to Assets Ratio (DAR), Debt To Equity Ratio (DER), Total Assets Turnover (TATO), and GR). After an IPO, only the CR grew in value. Keywords: financial performance, go public, Initial Public Offering (IPO), stock market, wilcoxon signed rank test